Family structure is associated with oral pain in 12-year-old Greek schoolchildren - ALLAN PAU, KONSTANTINOS GEORGIOS BAXEVANOS & RAY CROUCHER (IAPD and Blackwell, 2007)
Pain among children and adolescents has been identified as an important public health problem, with prevalence estimates reported to range from 9% for chest pain to 12% for tooth pain and 60% for headache.